Cardiovascular outcomes and systemic anti‐inflammatory drugs in patients with severe psoriasis: 5‐year follow‐up of a Danish nationwide cohort. (10th October 2014) - Ahlehoff, O.; Skov, L.; Gislason, G.; Gniadecki, R.; Iversen, L.; Bryld, L.E.; Lasthein, S.; Lindhardsen, J.; Kristensen, S.L.; Torp‐Pedersen, C.; Hansen, P.R.
Abstract Background Psoriasis is a common disease and is associated with cardiovascular diseases. Systemic anti‐inflammatory drugs may reduce risk of cardiovascular events. We therefore examined the rate of cardiovascular events, i.e. cardiovascular death, myocardial infarction and stroke, in patients with severe psoriasis treated with systemic anti‐inflammatory drugs. Methods Individual‐level linkage of administrative registries was used to perform a longitudinal nationwide cohort study. Time‐dependent multivariable adjusted Cox regression was used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs) of cardiovascular events associated with use of biological drugs, methotrexate, cyclosporine, retinoids and other antipsoriatic therapies, including topical treatments, phototherapy and climate therapy. Results A total of 6902 patients (9662 treatment exposures) with a maximum follow‐up of 5 years were included. Incidence rates per 1000 patients‐years for cardiovascular events were 4.16, 6.28, 6.08, 18.95 and 14.63 for biological drugs, methotrexate, cyclosporine, retinoid and other therapies respectively. Relative to other therapies, methotrexate (HR 0.53; CI 0.34–0.83) was associated with reduced risk of the composite endpoint and a comparable but non‐significant protective effect was observed with biological drugs (HR 0.58; CI 0.30–1.10), whereas no protective effect was apparent with cyclosporine (HR 1.06; CI 0.26–4.27) and retinoids (HR 1.80; CI 1.03–2.96). Tumour necrosis factor inhibitors (HR 0.46; CI 0.22–0.98) were linked to reduced event rates, whereas the interleukin‐12/23 inhibitor ustekinumab (HR 1.52; CI 0.47–4.94) was not. Conclusion Systemic anti‐inflammatory treatment with methotrexate was associated with significantly lower rates of cardiovascular events during long‐term follow‐up compared to patients treated with other antipsoriatic therapies. The treatment strategy in patients with severe psoriasis may have an impact on cardiovascular outcomes and randomized trials to evaluate the cardiovascular safety and efficacy of systemic antipsoriatic therapies are called for.